THEORETICAL FOUNDATIONS OF MEMORY PROCESSES AND THEIR SPECIFICITY IN PRESCHOOL AGE - Mamajonova Shohista Kamolovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the role of memory processes, one of the mental processes, in the study of preschool age.